2015
DOI: 10.1353/csd.2015.0032
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative Analysis of the Barriers College Students With Disabilities Experience in Higher Education

Abstract: Students with disabilities are increasingly enrolling in colleges and universities. However, many institutions are still unprepared to support them beyond the basic federal mandate of equal access and reasonable accommodations. This qualitative study utilized a nontraditional media of reflective journaling to capture the anecdotal experiences of 16 college students with disabilities for a 10-week period. Four major themes emerged concerning barriers and frustrations these students encountered on a daily basis:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
115
1
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(129 citation statements)
references
References 18 publications
8
115
1
5
Order By: Relevance
“…Otros trabajos han llegado a conclusiones similares, que coinciden en los mismos resultados y además, han estudiado cómo formar al profesorado universitario en materia de discapacidad (Debrand & Salzberg, 2005;Healey, Jenkins, Leach, & Roberts, 2001;Hockings & cols., 2012). En algunos de los estudios realizados se concluye que la actitud del profesorado mejora una vez que éste se forma y cuenta con más experiencia sobre cómo responder a las necesidades de los estudiantes con discapacidad (Hong, 2015;Murray & cols., 2011).…”
Section: Discusión Y Conclusionesunclassified
“…Otros trabajos han llegado a conclusiones similares, que coinciden en los mismos resultados y además, han estudiado cómo formar al profesorado universitario en materia de discapacidad (Debrand & Salzberg, 2005;Healey, Jenkins, Leach, & Roberts, 2001;Hockings & cols., 2012). En algunos de los estudios realizados se concluye que la actitud del profesorado mejora una vez que éste se forma y cuenta con más experiencia sobre cómo responder a las necesidades de los estudiantes con discapacidad (Hong, 2015;Murray & cols., 2011).…”
Section: Discusión Y Conclusionesunclassified
“…The barriers to participating in college for people with disabilities have been studied by many researchers. In one study (Hong, 2015), sixteen college students with various disabilities kept a journal about their student experience for 10 weeks. Students in this study often described college as stressful.…”
Section: Barriers To Participating In Collegementioning
confidence: 99%
“…The conclusions in this research continue to support previous research (Collins & Mowbray, 2005;Hong, 2015;Newman & Madaus, 2015) that suggested that classroom experiences, behaviors, and perceptions of students with disabilities interact during their higher education experience. The interaction of these dynamics, combined with the allocation of supports to provided educational access for students with disabilities, influences perception of campus climate.…”
Section: Chapter Five: Discussionsupporting
confidence: 85%